1997
DOI: 10.3109/00016359709091934
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of temporomandibular disorders in accordance with two classifications: the Helkimo dysfunction index and treatment need grouping

Abstract: We studied the fluctuation of temporomandibular disorders, applying two classifications systems, in a 2-year follow-up study of 411 subjects. In general, the fluctuation was not large. There were no major differences between the two classifications. In our opinion, a decision to treat a patient on the basis of the treatment need grouping would not lead to overtreatment. The study design suffered from the fact that it is not possible to separate the fluctuation of the TMD itself and the fluctuation of its signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…Symptoms came and disappeared without a demonstrable mutual relationship or predictable pattern within subjects, which is also seen in other studies. 22,23 In the subjects in this follow-up study at least bilaterally premolar support is present (Fig. 1).…”
Section: Discussionmentioning
confidence: 91%
“…Symptoms came and disappeared without a demonstrable mutual relationship or predictable pattern within subjects, which is also seen in other studies. 22,23 In the subjects in this follow-up study at least bilaterally premolar support is present (Fig. 1).…”
Section: Discussionmentioning
confidence: 91%
“…18,19 Masticatory muscle pain, TMJ sounds, limited jaw opening capacity, and deviations in mandibular movements are common signs and symptoms of TMD, which tend to fluctuate with temporary remissions. 6,20 The actual role of occlusion in the etiology of TMD has been widely debated. 21,22 It has been speculated that TMD is closely associated with some types of malocclusions, such as posterior crossbite, open bite, and deep bite, and the elimination of occlusion interference plus achievement of an occlusion system with no shift between CR and MI should be the primary goals of orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the longitudinal studies from the last two decades have reported a fluctuation in the signs and symptoms of TMD [25] with no predictable pattern [1,17,19,23,29,32,34]. Only a few studies have assessed the fluctuating nature of TMD in the age group with highest incidence of TMD (20-50 years) [19,20,28,29,31,34,43].…”
Section: Introductionmentioning
confidence: 99%
“…Viele longitudinale Studien der letzten zwei Jahrzehnte konnten die ausgeprägte Fluktuation von TMD-Befunden und -Symptomen über die Zeit zeigen [25], welche scheinbar ohne ein vorhersehbares Muster verläuft [1,17,19,23,29,32,34]. Jedoch haben nur wenige longitudinale Studien die Fluktuation von TMD in der Altersphase mit höchster TMD-Inzidenz (20-50 Jahre) untersucht [19,20,28,29,31,34,43].…”
Section: Introductionunclassified